Zearalenone Promotes Cell Proliferation or Causes Cell Death? - Zheng, Wanglong; Wang, Bingjie; Li, Xi; Wang, Tao; Zou, Hui; Gu, Jianhong; Yuan, Yan; Liu, Xuezhong; Bai, Jianfa; Bian, Jianchun; Liu, Zongping (My University, 2018)
Zearalenone (ZEA), one of the mycotoxins, exerts different mechanisms of toxicity in different cell types at different doses. It can not only stimulate cell proliferation but also inhibit cell viability, induce cell apoptosis, and cause cell death. Thus, the objective of this review is to summarize the available mechanisms and current evidence of what is known about the cell proliferation or cell death induced by ZEA. An increasing number of studies have suggested that ZEA promoted cell proliferation attributing to its estrogen-like effects and carcinogenic properties. What’s more, many studies have indicated that ZEA caused cell death via affecting the distribution of the cell cycle, stimulating oxidative stress and inducing apoptosis. In addition, several studies have revealed that autophagy and some antioxidants can reverse the damage or cell death induced by ZEA. This review thoroughly summarized the metabolic process of ZEA and the molecular mechanisms of ZEA stimulating cell proliferation and cell death. It concluded that a low dose of ZEA can exert estrogen-like effects and carcinogenic properties, which can stimulate the proliferation of cells. While, in addition, a high dose of ZEA can cause cell death through inducing cell cycle arrest, oxidative stress, DNA damage, mitochondrial damage, and apoptosis.
Citation: Zheng, W.; Wang, B.; Li, X.; Wang, T.; Zou, H.; Gu, J.; Yuan, Y.; Liu, X.; Bai, J.; Bian, J.; Liu, Z. Zearalenone Promotes Cell Proliferation or Causes Cell Death? Toxins 2018, 10, 184.
Keywords: Apoptosis; Cell Death; Cell Proliferation; Estrogen-Like Effects; Zearalenone